Design of modern academic laboratories based on VDI infrastructure - Chrobak, Paweł (Business Informatics, 2014)
The article describes the causes of the economic and organizational case for implementing VDI solutions in the learning centers of Academic Centers. The analysis laboratory infrastructure allows for better understanding the broad ability to adapt to VDI and range of benefits they receive, administrators and staff research and teaching. Described implementation is based on VMware Horizon View 5.The author was the originator of the concept of VDI implementation at the University of Economics in Wrocław and participant of the project team
Informatyka Ekonomiczna = Business Informatics, 2014, Nr 3 (33), s. 34-45
Keywords: Private cloud; virtualization; VDI infrastructure; desktop as a service; student lab; chmura prywatna; wirtualizacja; infrastruktura VDI; laboratorium dydaktyczne